Design and implementation of bandwidth monitoring, line aggregation of VoIP - Oo, Tun Tun (Animo Repository, 2019)
Nowadays, there are many ways to get the Internet connection such as ADSL, Mobile, Wifi, WiMax, Fttx. Furthermore, the Internet connection can get anywhere and any times. In fact, the PBX systems would be low interested because the PBX (Private Branch Exchange) is used circuit switching system and is also used to expend the phone bills [1]. The VoIP system uses the packet switching which it can use everywhere in the place of getting an Internet connection. Moreover, the Phone bill costs are lowest and flexible to use in the new era. In this paper, the VoIP technology is used bandwidth control and line aggregation to get the network speed in the network infrastructure. Moreover, the traffic and bandwidth of each port and whole systems can monitor and manage. In this paper, the OSPF, Ether channel and bandwidth monitoring system are used in real time simulations. All of systems are used the Cisco devices, Linux and windows OS and line aggregations. Line aggregation means line compositions. One switch port can use 100 Mbps/ 1Gbps. On the other hand, if the port is 1Gbps, the four ports are used that it may be 4Gbps. Moreover, not only line combination, but also link redundancy. In this paper, the Gns3 simulation is mainly emulated in the virtual environment with VMware. GNS3 (Graphical Network simulator) allows simulation of complex network structure and the outside world. It can interoperate and communication together with VMWare workstation, Virtual Machine and Esxi to imitate various OS in a virtual community such as Linux, Windows OS and Cisco IOS. GNS3takes this a step further by providing a graphical environment. © 2019, World Academy of Research in Science and Engineering. All rights reserved.